Pengaruh Pupuk Organik Cair Kasgot Terhadap Pertumbuhan dan Produksi Tanaman Cabai (Capsicum Frutescens) Varietas Sonar dalam Keadaan Cekaman Air - Baene, Gadis Manis; Zulfida, Ida; Sibagariang, Edison (JURNAL AGROPLASMA, 2023)
Capsicum frutescens is one of the top commodities of horticultural plants in Indonesia which is a type of vegetable that is very high potential and provides great benefits for farmers. One of the good fertilizers used on the rawit pepper plant is liquid organic fertilizer of kasgot. The physiological survival of rawit pepper plants depends on the availability of water in the soil which is a basic need for plants. This study uses a complete random design. (RAL). Treatment with two factors where the first factor is liquid organic fertilizer cascade (K) with three dimensions, namely; K0 : control, K1 : 20 ml/liter, K2 : 30 ml /liter and the second factor of water decay (C) with a three dimensional is; C1 : 100% KL (750 ml), C2 : 75% KL (562 ml); C3 : 50% KL (375 ml). The observed parameters are the height of plants (cm), diameter of stems (mm), number of leaves (leaves) and age of flowers. Graft analysis with graft analysis (Anova), continued with a DMRT test at the level of 0.05, if there is a marked effect of treatment. The average height of the rawit pepper plant that gives the highest result is at treatment K2 = 30 ml and C2 = 50% KL (562 ml) is 86.94 cm. The best treatment for the parameter number of leaves is K2 = 30 ml and C1 = 100% KL (750 ml) is 57,56 cm. The treatment that gives the best value is in K2 = 30 ml and C2 = 75% KL (562 ml) is 9.81 (mm). The best treatment on the flower age parameters is, K2 = 30 ml and C3 = 50% KL (357 ml). Keywords: Cayenne pepper, Kasgot Fertilizer, Water Stress